A Block Classification Method with Monitor and Restriction in NAND Flash memory - Myungsub Lee (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Flash memory has the advantages of fast access speed, low power consumption, and low price. Therefore, it is widely used in many sectors of the electronics industry. However, the flash memory also has a disadvantage of a limited number of P/E (Program/Erase) cycles. Many wear-leveling techniques have been studied to prolong the lifetime of flash memory by equalizing the P/E cycles of the blocks. This paper proposes BCMR (a Block Classification with Monitor and Restriction) method to isolate and reduce the interference of blocks in garbage collection and wear leveling. The BCMR method monitors the endurance variation of blocks during garbage collection and detects hot blocks by making a restriction condition based on this information. This method induces block classification by its update frequency for garbage collection and wear leveling, resulting in a prolonged lifespan for NAND (Not AND) flash memory systems. This paper shows the block standard deviation, which was reduced by up to 11% when BCMR was implemented. And we show the average number of page migrations during garbage collection and wear leveling, which was reduced by about 1% when BCMR was activated. The performance evaluation results show that the BCMR method prolonged the life of NAND flash memory systems by 3.95% and reduced the standard deviation per block by 7.4%, on average.